Workshop on Simple and Cool Ways to Make a Restaurant Cashier Application with PHP + JavaScript - Rustam, Muhammad Taufiq; Muhatri, Muhatri; Nasution, Adnan Buyung (PT FORMOSA CENDEKIA GLOBAL, 2023)
This workshop aims to provide insight and skills to participants in creating restaurant cashier applications using PHP and JavaScript in a simple and interesting way. Through an introduction to basic cashier application concepts and practical steps, participants will be guided through the application creation process, with code examples and in-depth instructions. The choice of PHP and JavaScript as development technologies was based on their popularity and ease of integration, while this workshop was designed to ensure that participants of all skill levels could easily follow and implement an effective restaurant cashier application. The results of the workshop include the development of a restaurant cashier application that can be adopted and adapted by participants according to their business needs. Apart from screenshots or short demonstrations of the applications that have been created, this workshop also discusses evaluating the advantages and disadvantages of using PHP and JavaScript in the context of creating restaurant cashier applications. By providing opportunities for participants to actively engage in learning and contribute to discussions, this workshop is expected to increase their understanding and skills in developing practical information technology solutions for the restaurant industry.